2014
DOI: 10.1098/rsbl.2014.0309
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing: resource provisioning alters infectious disease dynamics in wildlife

Abstract: Provisioning of abundant food resources in human-altered landscapes can have profound effects on wildlife ecology, with important implications for pathogen transmission. While empirical studies have quantified the effects of provisioning on host behaviour and immunology, the net interactive effect of these components on host-pathogen dynamics is unknown. We use simple compartmental models to investigate how provisioning-induced changes to host demography, contact behaviour and immune defence influence pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 20 publications
3
125
0
Order By: Relevance
“…). Increased concentrations of small mammals at feeder sites will reach an asymptote, however, as larger group sizes may facilitate disease and parasite transmission (Becker and Hall , Sorensen et al. , Forbes et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Increased concentrations of small mammals at feeder sites will reach an asymptote, however, as larger group sizes may facilitate disease and parasite transmission (Becker and Hall , Sorensen et al. , Forbes et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Zelenski and Nisbet ). Potential negative implications of bird feeding include increased disease transmission (Becker and Hall , Adelman et al. ), increased risk of predation (Dunn and Tessaglia ) or mortality related to window‐strikes near feeders (Kummer and Bayne ) and changes in evolutionary trajectories (Plummer et al.…”
Section: Introductionmentioning
confidence: 99%
“…For the opposite result in an urban habitat, supplemental feeding (garbage and deliberate feral animal feeding by residents) on St. Simons Island might have led to higher tolerance by raccoons toward conspecific animals, which may reduce aggressive (60) behavior, reducing the likelihood of fighting and hemoplasma transmission through infected blood or saliva. Higher food availability or quality in urban habitats (if raccoons were being fed nutritionally rich supplements, such as cat food) could allow heavier raccoons to mount a more successful immune defense against hemoplasma (61). Additional routes of transmission for hemoplasmas, such as transplacental and transmammary transmission (32), may also influence differences in hemoplasma prevalence, particularly if one population has a different population age structure.…”
Section: Resultsmentioning
confidence: 99%
“…Plowright et al [25] demonstrated that the effects of urban development on these metapopulations, through increased contact with humans and horses, and reduced connectivity between flying fox colonies, could dramatically influence the epidemic dynamics of the virus in flying foxes, and increase the risk of Hendra virus emergence in horses and people. Using mechanistic models, Becker and Hall [82] and Becker et al [78] also demonstrated host demographic, contact and immunological effects of provisioning on R 0 , finding that unless provisioning reduces dietary exposure to pathogens or strongly improves host condition and immunity, increased aggregations of wildlife species dramatically increase pathogen invasion success and long-term prevalence. Environmental stressors such as heavy metal and pesticide pollutants, characteristic of certain urban environments, can further compound these outcomes through their effects on immunological function [83].…”
Section: Interfaces Between Sympatric Wildlife Livestock and Humans mentioning
confidence: 99%